Effect of sustainable hydroponic substrates on biomass and essential oil of Plectranthus amboinicus (Orinoquia, 2026)
The effect of four hydroponic substrates on the growth kinetics, biomass accumulation, and essential oil yield of Plectranthus amboinicus (Lour.) Spreng. was evaluated under tropical conditions in Puerto López, Colombia. A completely randomized design was used with four treatments: river sand (T1), coconut fiber + rice husk mixture 1:1 (T2), rice husk (T3), and pure coconut fiber (T4), with five replicates. Height growth fitted a logistic model (R2 > 0.99), and T2 and T4 showed the highest maximum growth rates (5.88 and 5.53 cm/week). At the end of the cycle, T4 recorded the highest total fresh biomass (880.00 g/plant), fresh leaf biomass (554.22 g/plant), and dry leaf biomass (66.62 g/plant). The highest essential oil yield obtained by microwave-assisted hydrodistillation was observed in T4 (0.748 % on a dry basis; 0.090 % on a fresh basis), followed by T2 (0.577 %), T3 (0.434 %), and T1 (0.320 %). Under the evaluated conditions, coconut fiber favored biomass accumulation and essential oil yield, making it a promising substrate for tropical hydroponic systems of P. amboinicus.
Keywords: coconut fiber; essential oil; hydrodistillation; growth kinetics; logistic model; Cuban oregano